Research on the Withstand Voltage Properties of Cr/Mn-Doped Al2O3 Ceramics in Vacuum - Dandan Feng; Xiaojing Wang; Xueying Han; Zhiqiang Yu; Jialun Feng; Hefei Wang (Electronic Materials)
Al2O3 ceramics are widely used in vacuum electronic devices. However, surface flashover in a vacuum during the application of high voltage significantly influences their reliability and restricts the development of vacuum electronic devices. The secondary electron emission yield (SEY) and surface resistivity of ceramics are the main factors affecting the vacuum withstand voltage of ceramic materials. In this study, the bulk density, microstructure, and surface properties—including SEY and surface resistivity—of Al2O3 ceramics were tested. The relationship between these properties and the vacuum withstand voltage of the ceramics was investigated. The influence of the addition ratio of Cr2O3 to MnO2 and the sintering temperature was investigated. The results show Cr/Mn-doped Al2O3 ceramics, with appropriate amounts of Cr2O3 and MnO2 and sintered at suitable temperatures, exhibit low SEY, high withstand voltage, and excellent stability in vacuum.